Research on certificate information authentication method of expressway toll based on blockchain technology - Xiaoming LIU; Chunlin SHANG; Jie ZHANG; Jie CHEN; Xiangda WEI; Guiqing ZHU (智能科学与技术学报)
With the continuous development of expressways convenient and non-feeling toll collection,reliable travel trajectory certification has gradually become the key support for fair and accurate toll collection.In view of the problems of high vehicle inspection delay,high time consuming of massive data retrieval,and low tampering data inspection accuracy,the multi-agent and multi-stage operation characteristics of expressway vehicles were considered,started with the dynamic certification of high-speed vehicle driving process and the safety association certification of vehicle information,the characteristics of multi-stage authentication content analysis,distributed network authentication consensus,vehicle information main chain association and vehicle trajectory side-chain tracking were considered,a reliable driving track authentication method for expressway based on heterogeneous blockchain technology was proposed,which realized the real-time inspection of vehicle information and the reliable track authentication of expressway vehicles based on track information chain association.Finally,through the introduction of typical application scenarios of the method,the prospect and value of the method in the certification of highway vehicle trajectory were further analyzed.